Internet use and human values: Analyses of developing and developed countries. (September 2015) - Bagchi, Kallol K.; Udo, Godwin J.; Kirs, Peeter J.; Choden, Khendum
Highlights: We use Schwartz's model to explore the impact of values on individual internet use. Study 1 uses 49 developed and emerging nations based on World Value Survey data. Study 2 uses 8 nations developed and emerging based on European Social Survey data. From Study 1 Schwartz-like value types are significant on Internet use in both groups. Study 2: tradition and security are most relevant and different impact in each group. Abstract: In this study, we use Schwartz's value framework to explore the impact of values on internet use at an individual level. This approach differs from many of the previous studies that report on national level analyses. The gap in the literature arising from the absence of Schwartz's value types in information and communication technologies (ICT) studies calls for investigation of the impact of individual values on ICT use at the individual level. For study 1, we use the set of developing and developed nations, based on World Values Survey data. For study 2, we use eight nations grouped into two economic/cultural clusters (developed and developing) based on the data from the European Social Survey. Study 1 findings indicate that 4 out of 8, 6 out of 8 and 7 out of 8 Schwartz-like human value types are significant for Internet use for developed, developing and all nations respectively, with robust effect sizes. The study 2 findings indicate that for developed nations, Schwartz value types such as conformity, tradition, security, and power are relevant in at least two or more out of the four nations. In the case of the developing nations, achievement, stimulation, self-direction, tradition and security are relevant in at least two or more out of four nations. Tradition and security are the two value types that are most relevant in both groups of nations. These results indicate that value types have different as well as similar impacts in developed and developing nations. Similarities and differences also exist within developed and developing nations. The results show that value types in general and Schwartz's value types in particular, are useful in explaining Internet use. The implications of these findings are discussed and future studies suggested.